1992
DOI: 10.1002/ijc.2910500424
|View full text |Cite
|
Sign up to set email alerts
|

Stimulation of the metastatic properties of lewis‐lung‐carcinoma cells by autologous granulocyte‐macrophage colony‐stimulating factor

Abstract: Using both polymerase-chain-reaction analysis and the soft-agar colony-forming unit assay, granulocyte-macrophage colony-stimulating factor (GM-CSF) was shown to be expressed by cloned metastatic Lewis-lung-carcinoma (LLC-LN7) cells but not by non-metastatic LLC-C8 cells. Furthermore, the metastatic LLC-LN7 cells were shown to respond both to autologous GM-CSF and to exogenous recombinant GM-CSF (rGM-CSF). In the presence of neutralizing anti-GM-CSF antibodies, the metastatic LLC cells became less able to migr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
13
2

Year Published

1993
1993
2012
2012

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 23 publications
(16 reference statements)
3
13
2
Order By: Relevance
“…A relevant example of a cell type whose metastatic and migratory actions are dependent upon GM-CSF is Lewis lung carcinoma. GM-CSF is produced by a metastatic strain of these cells, but not by a nonmetastatic strain; neutralizing anti-GM-CSF antibodies decrease the ability of the metastatic strain to undergo migration and invasion [50]. Cellular migratory capability may be an important biological parameter: Partin et al [51] have obtained evidence that a malignant prostate cell's migratory ability correlates with its metastatic potential.…”
Section: Discussionmentioning
confidence: 98%
“…A relevant example of a cell type whose metastatic and migratory actions are dependent upon GM-CSF is Lewis lung carcinoma. GM-CSF is produced by a metastatic strain of these cells, but not by a nonmetastatic strain; neutralizing anti-GM-CSF antibodies decrease the ability of the metastatic strain to undergo migration and invasion [50]. Cellular migratory capability may be an important biological parameter: Partin et al [51] have obtained evidence that a malignant prostate cell's migratory ability correlates with its metastatic potential.…”
Section: Discussionmentioning
confidence: 98%
“…Young et al 51 described a stimulation of the migratory and metastatic potential in Lewis lung carcinoma cells by GM-CSF. Others showed the association of GM-CSF expression with a metastatic phenotype in solid tumors of mouse and human origin.…”
Section: Discussionmentioning
confidence: 99%
“…The main finding of our study is that IGF I, IGF II, HGF, EGF and SCF stimulate cell migration of human non-SCLC cell lines in a dose-dependent manner. Even though rhGM-CSF, synthetic hCGRP, bombesin, bovine insulin and rhIL-6 have been shown to stimulate migration of normal and tumor cells (Ruff et al, 1985;Sanghavi et al, 1994;Sehgal and Tamm, 1991;Shoji et al, 1990;Young et al, 1992;Kohn et al, 1990), they did not stimulate motility in the lung-cancer cell lines examined by us.…”
Section: Discussionmentioning
confidence: 83%
“…IGF II induced both chemotactic and chemokinetic motility and, in vivo, may play a role in the local invasive action of tumor cells, possibly acting in an autocrine and/or a paracrine fashion. The growth and motility of established mesothelioma and lung-cancer cell lines is stimulated by various growth factors (Klominek et al, 1998a,b;Young et al, 1992). In addition, we have shown that certain factors stimulate autocrine motility in the Wart cell line (Klominek et al, 1998c).…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation